ANALISIS PENETAPAN HARGA POKOK PRODUKSI (HPP) PADA USAHA MIKRO KECIL JALANGKOTE SALAHUTU DI KOTA MAKASSAR - Adiaksa, Harvan; Azis, Muhammad; Idris, Hariany (Jurnal Sains Riset, 2024)
This study aims to: know and analyze the Determination of Cost of Goods Produced (COGS) in Jalangkote Salahutu Micro Small Enterprises (MSEs) in Makassar City. This study is based on analyzing the determination of the cost of goods produced (COGS) at UMK Jalangkote Salahutu in Makassar City whether the costs involved are in accordance with the selling price that has been set. The data collection techniques used were interviews and documentation. Data analysis techniques use qualitative descriptive analysis. This technique begins with collecting the required data in the form of data and cost information and other supporting evidence, conducting interviews with business owners or owners, processing interview results, and administrative data obtained based on the analysis of the data used and calculating it with the full costing method, describing the method of determining the cost of goods produced in MSEs, and drawing conclusions. Based on the results of the study that: (1) Cost of Goods Produced that has been carried out by researchers shows that the cost of goods produced in UMK Jalangkote Salahutu products is Rp. 2,979 in Jalangkote products, Rp. 5,338 in Spring Roll products, Rp. 5,354 in Croquette products, Rp. 5,265 in Bikang Doang products. While the selling price set by the company is Rp. 7,000. (2) Looking at the comparison between the cost of goods produced and the selling price of the product, the business owner earns a profit of Rp. 4,021 on Jalangkote products, Rp. 1,662 on Spring Roll products, Rp. 1,646 on Croquette products, Rp. 1,753 on Bikang Doang products.Keywords: Cost of Goods Produced